G. DÁWLETOVA SHIĠARMALARINDA METAFORALARDIŃ STILLIK QOLLANILIWI - Jolımbetova, Sh.A. (SCIENCE and SOCIETY, 2022)
The given article deals with one of the problems of the Turkic Language, which is closely related with the actual issue of Modern karakalpak stylistics, and special affention is given to troops. This field of area Karakalpak stylistics even enough investigated, it requires comprehensive investigation. There are some supporting examples from poet of Karakalpak Literature G.Davletova’s work, especially we analyse deeple metaphors of the works.